Synthesis and Structure–Activity Relationship of Novel Indole Acrylamide Derivatives as HCV Replication Inhibitors. (January 2015) - Son, Seohyun; Kim, Dahee; Lee, Sungjin; Jin, Guanghai; Park, Jin‐Ah; Han, Hyo‐Kyung; Lee, Kyeong; Lee, Choongho
<x xml:space="preserve">Abstract</x> A series of indole acrylamide derivatives were synthesized and evaluated for their inhibitory effects on hepatitis C virus (HCV) replication. Previously, we have identified (E)‐N‐(4‐tert‐butylphenyl)‐3‐(5‐cyano‐1H‐indol‐3‐yl)‐2‐methylacrylamide (6c) as one of the promising leads for anti‐HCV chemotherapy. Based on the structural features of indole acrylamide, we have explored extended structure–activity relationship study using analogs with substituted indoles, various amides, and N‐substitution at the indole ring. Among the newly synthesized series, 5‐cyanoindole acrylamide analog with N‐acetyl substitution (13c) (EC50 = 0.98 μM, CC50 = 40.74 μM, and SI = 41.6) exhibited the most potent antiviral activity with reasonable cytotoxicity in a cell‐based J6/JFH1 reporter assay using Huh7.5 cells. In addition, improved water solubility of 13c compared to 6c further merits consideration of 13c as a valuable candidate for anti‐HCV therapeutics development.